A Simple Organic Molecule Realizing Simultaneous TADF, RTP, AIE, and Mechanoluminescence: Understanding the Mechanism Behind the Multifunctional Emitter. Issue 49 (21st October 2019) - Zhan, Lisi; Chen, Zhanxiang; Gong, Shaolong; Xiang, Yepeng; Ni, Fan; Zeng, Xuan; Xie, Guohua; Yang, Chuluo
Abstract: Aggregation‐induced emission (AIE), thermally activated delayed fluorescence (TADF), room‐temperature phosphorescence (RTP), and mechanoluminescence (ML) have attracted widespread interest. However, a multifunctional organic emitter exhibiting simultaneous AIE, TADF, RTP, and ML has not been reported. Now, two multifunctional blue emitters with very simple structures, mono‐DMACDPS and Me‐DMACDPS, exhibit typical AIE, TADF, and RTP properties but different behavior in mechanoluminescence. Crystal structure analysis reveals that large dipole moment and multiple intermolecular interactions with tight packing mode endow mono‐DMACDPS with strong ML. Combined with the data of crystal analysis and theoretical calculation, the separated monomer and dimer in the crystal lead to the typical TADF and RTP properties, respectively. Simple‐structure mono‐DMACDPS is the first example realizing TADF, RTP, AIE, and ML simultaneously. Abstract : Multifunctional organic emitter : One simple organic molecule exhibits aggregation‐induced emission (AIE), thermally activated delayed fluorescence (TADF), room‐temperature phosphorescence (RTP), and mechanoluminescence (ML) simultaneously.